Sistem Untuk Pengendalian Manejemen Dalam Upaya Kinerja Perusahaan Dan Daya Saing Untuk Mempertahankan Keberlangsungan Operasinya - Khadafi, Muammar; Yanti, Mirna; Aprillia, Meisya; Riska, Riska; Raihan, Cut (Ecobankers : Journal of Economy and Banking, 2024)
The management control system is a way to control company performance. The basis for creating balance and conformity to achieve effectiveness and efficiency in order to achieve maximum profits for the company. Management control systems are created to maintain the company's sustainability and remain stable and to increase the company's competitiveness, even though the company focuses on services. Management control not only addresses problems from within the company itself but also from outside, for example competitiveness. With high competitiveness, companies can maintain the continuity of their operations. Key factors in the success of a Management Control System involve employee involvement, transparency of information, and adaptability to changes in the business environment. This research provides valuable insight for companies in designing and improving their Management Control Systems, with the hope of contributing to the development of management theory and practice. In conclusion, in this case the management control system is not only an internal control tool, but also a strategy that can support growth and also for company sustainability in a dynamic business era.